Administrative discretion in the field of administrative control and judicial oversight thereof: An analytical study - Sharif, Dr.Rizan Saeed Hama Sharif (Sulaimani Journal for Humanities, 2025)
In our present era, individuals are entitled to enjoy rights and freedoms, but not absolutely or without limits. Any freedom or right, if exercised unrestrained, can lead to chaos that infringes upon the rights and freedoms of others. Therefore, freedom must be regulated by the relevant authorities, known as "administrative control," through legally established safeguards. This is what is called the administrative function, which is to protect public order. The legislator has assigned this function to the executive branch by virtue of its nature and its practical ability to intervene swiftly to protect public order, in addition to its constitutionally mandated task of implementing laws. Thus, the exercise of administrative control is a natural consequence of implementing laws that stipulate the preservation of public order. The importance of administrative control remains clear, especially when the administration exercises its discretionary power. The administration's activity, with its inherent restrictions on individual freedoms, whether in ordinary or exceptional circumstances, constitutes a highly dangerous power with serious repercussions for public liberties. This activity also presents an opportunity for administrative control bodies to deviate from their defined objective of maintaining public order. Therefore, we will examine this topic in two sections, the first of which will focus on... The first of them is to define the discretionary power of the administration and its oversight in the field of administrative control, and we will dedicate the second section to defining administrative control and judicial oversight of it, and in the conclusion we will refer to the most important conclusions and recommendations that we have reached.